Converting Bi-Level Positive Airway Pressure Machines into Ventilators for Hospitalized Coronavirus Disease-2019 Patients: Emergency Use Protocol - Hugh A. Cassiere; Stanley John; Todd Goldstein (Research and Practice in Anesthesiology, 2021)
During March 2020 New York State was facing a shortage of tens of thousands of ventilators. City and state officials were rapidly trying to source more of the machines, which were required in the sickest patients who were critically-ill with coronavirus disease-2019 (COVID-19).